2022
DOI: 10.24251/hicss.2022.389
|View full text |Cite
|
Sign up to set email alerts
|

The Political Turn of Twitch – Understanding Live Chat as an Emergent Political Space

Abstract: Research and media have all emphasized the importance of digital platforms such as Twitter and Facebook in contemporary political activism. Yet, little is known of the politicization of other digital platforms, such as Reddit, Twitch, and Discord, and how such politicization is manifested. By politicization, we refer to the emergence of political messages in a "decidedly a-political" space. In this paper, we explore a case of politicization on Twitch, a live streaming platform associated with the gaming commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Indeed, the community has found a way to adapt the platform to its own interests (e.g. The 2019-2020 Hong Kong protests; Ruiz-Bravo et al, 2022). Such stepping outside the framework officially set by the stakeholders is extremely interesting as it shows an emergent property of the system, in the sense that it is the infrastructure, the channel, that is central here, while prior contents and alleged, official uses are secondary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the community has found a way to adapt the platform to its own interests (e.g. The 2019-2020 Hong Kong protests; Ruiz-Bravo et al, 2022). Such stepping outside the framework officially set by the stakeholders is extremely interesting as it shows an emergent property of the system, in the sense that it is the infrastructure, the channel, that is central here, while prior contents and alleged, official uses are secondary.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have presented a broader understanding of the platform and used Twitch to answer more general research questions. For example, Ruiz-Bravo et al (2022) showed how users have found ways to use gameplay to promote political activism, demonstrating Twitch's potential as a political space. Riddick and Shivener (2022) used Twitch to study the 'affective spamming', a visual-content-based form of spam that online audiences use to influence public communication and deliberation on social media during live events.…”
Section: Introductionmentioning
confidence: 99%
“…As seen above, most Twitch studies to date have focused on the platform, gaming, interaction, the community, monetisation of activity, advertising, and mental health. However, over the years the scientific community has started answering more diverse questions about the platform, including societal issues such as climate change (Navarro & Tapiador, 2023), and politics (Ruiz-Bravo, Selander & Roshan, 2022;Iranzo-Cabrera & Casero-Ripollés, 2023), among others. These authors concur in pointing out the diversity and heterogeneity of the space that is created on Twitch, which is far removed from the polarised discourses found on other social networks such as X or Facebook.…”
Section: Twitchmentioning
confidence: 99%
“…As an exception we should point out the exploratory study that Ruiz-Bravo et al [ 65 ] have made of the usage of live chats in e-games channels for promote political activism, related to the protests in Hong Kong in 2019. However, Twitch remains unexplored from the point of view of political communication and its connection with democracy.…”
Section: Literature Reviewmentioning
confidence: 99%